ANALGESIC PROPERTY OF ANGIOTENSIN AT1 RECEPTOR ANTAGONIST: CANDESARTAN IN RATS AND MICE - Jadhav, Asha D; Jadhav, Rakesh R; Padwal, Sudhir L; Deshmukh, Vinod S; Pise, Harshal N; Jadhav, Swapnil S (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: The objective was to evaluate analgesic activity of candesartan in graded dose in tail flick method in rats and acetic acid-induced writhing in mice. Methods: Wistar Albino rats of either sex weighing 200-250 g or Swiss Albino mice of either sex weighing 20-25 g. Analgesic activity of candesartan (5 mg/kg, 10 mg/kg, 15 mg/kg.) was evaluated in graded dose and compared with tramadol (10 mg/kg) and aspirin (100 mg/kg) using tail flick response method and acetic acid-induced writhing of analgesia. Study was conducted after approval from the Institutional Animal Ethics Committee, which is an approved body by Committee for the Purpose of Control and Supervision of Experiments on Animals letter no. 78 dated October 18, 2012. Results: In the present study, oral administration of candesartan showed analgesic activity at high dose compared to the control and less analgesic activity as compared to the standard in analgesic methods. In tail-flick method, after 30-90 minutes of drug administration, tail flick latency of candesartan (15 mg/kg) was significant (p<0.05) compared with control but less than that of tramadol and aspirin. In acetic acid induced writhing method, the analgesic activity of candesartan was significant only at high dose (15 mg/kg) compared to the control. Conclusion: Candesartan possesses analgesic activity only at high dose. However, further studies need to be carried out to see underlying mechanism candesartan in analgesia and to know the extent of analgesia. Keywords: Acetic acid induced writhing method, Angiotensin II receptor blockers, Candesartan, Tail flick method